Specification for phenol (BSI, 1964)
Phenol, Phenols, Solubility, Solubility test methods, Crystallization, Boiling point, Temperature measurement, Samples, Determination of content, Water content determination, Chemical analysis and testing, Evaporation residue determination, Test equipment, Sampling methods